2019
DOI: 10.1249/mss.0000000000001935
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Behavior and Health: Update from the 2018 Physical Activity Guidelines Advisory Committee

Abstract: Purpose: To provide an overview of relationships between sedentary behavior and mortality as well as incidence of several non-communicable diseases and weight status reported in the 2018 Physical Activity Guidelines Advisory Committee Scientific Report (2018 PAGAC Scientific Report), and to update the evidence from recent studies.Methods: Evidence related to sedentary behavior in the 2018 PAGAC Scientific Report was summarized and a systematic review was undertaken to identify original studies published betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
273
2
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(288 citation statements)
references
References 39 publications
4
273
2
9
Order By: Relevance
“…In recent years, there has been a rapid accumulation of studies highlighting the distinct and harmful effects of SB on health outcomes. The 2018 United States Physical Activity Guidelines Advisory Committee (PAGAC) released a scientific report on SB and health, which found strong evidence of a dose-response relationship between both total SB and TV viewing and incident cardiovascular disease, as well as all-cause and cardiovascular disease mortality [40]. For instance, one meta-analysis reported that the risk of all-cause and cardiovascular disease mortality increased above a threshold of 6 to 8 h per day for total SB and 3 to 4 h per day for TV viewing [5].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a rapid accumulation of studies highlighting the distinct and harmful effects of SB on health outcomes. The 2018 United States Physical Activity Guidelines Advisory Committee (PAGAC) released a scientific report on SB and health, which found strong evidence of a dose-response relationship between both total SB and TV viewing and incident cardiovascular disease, as well as all-cause and cardiovascular disease mortality [40]. For instance, one meta-analysis reported that the risk of all-cause and cardiovascular disease mortality increased above a threshold of 6 to 8 h per day for total SB and 3 to 4 h per day for TV viewing [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, subjective assessments of sedentary behavior in one domain may not be a valid measure of the total amount of daytime SED [43]. SED has been shown to be a risk factor for metabolic health, that is partly independent of aerobic fitness and MVPA [32] (but see also [44,45]). It would therefore be expected that higher %SED would be associated with worse rather than better cognitive functions, especially among low fit individuals.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of sedentary behaviour (sitting) have been shown to be detrimentally associated with a number of physical and mental health outcomes [1][2][3]. For example, the U.S. 2018 Physical Activity Guidelines Committee concluded that there was "strong evidence for a direct association between greater amounts of sedentary behavior and higher risk of mortality from all-causes and CVD, and for higher risk of type 2 diabetes and CVD" [4]. Moreover, with trends towards greater sitting in the workplace [5], office workers have been shown to engage in high levels of sitting [6].…”
Section: Introductionmentioning
confidence: 99%